Perirectal metachronous recurrence of the hepatocellular carcinoma in the rectum on the 11C choline PET–CT - Fathinul Fikri, A.S; Noordzij, W. (Oxford University Press, 2021)
A 48-year-old female presented with a history of multicentric hepatocellular carcinoma (HCC). She had a complete tumour removal via local excision and radiofrequency ablation without tumour recurrence. On follow-up, she underwent 11C choline positron emission tomography-computed tomography (PET-CT) for tumour restaging, given the raised serum alfa-fetoprotein (AFP). Fused axial and coronal 11C choline PET–CT showed an 11C choline-avid mass (SUVmax: 17.9 g/dl) in the right upper perirectal region (arrowed) (Fig. 1). An enhanced, contrasted axial CT image confirmed the presence of an exophytic rectal wall mass with an indistinct tumour-rectal fat plane at the 11 o’clock position (arrowed) (Fig. 2). The anterior resection of the upper rectum and end-to-end anastomosis was performed. Solid fields of polygonal cells met the hepatoid aspect, in the fibrous stroma with an invasion of the muscularis propria of the rectal wall (multiple arrows). Tumour cells had polymorph nuclei, chromatine and eosinophilic granular cytoplasm. Immunohistochemistry showed expression of arginase, heppar-1 and BSEP, typical for hepatic origin (Fig. 3). A perirectal metachronous HCC in the rectum is exceedingly rare, which may be rendered inconspicuous on conventional imaging studies. In this case, the 11C choline was an important marker in underpinning the proliferation of the phospholipids in the cell membranes of the tumour. It is hypothesized that, based on the histology finding that the tumour epicentre was located deep in the subserosa, the hepatofugal portal or inferior vena cava dissemination of the primary HCC was the likely mode of the tumour spread.